THE USE OF THE BARK AS AN ENERGY RESOURCE IN THE COMPOSITION OF PINE WOOD PELLETS - Opryshko, O.; Pasichnyk, N.; Opryshko, N.; Zubkov, I. (Енергетика і автоматика, 2016)
The influence of the bark content in pine pellets on their mechanical strength is studied. It is shown that wood pellets made from bark and branches have static bending strength compared with standard samples made of sawdust.